Parental psychological control, psychological need satisfaction, and non-suicidal self-injury among Chinese adolescents: The moderating effect of sensation seeking. (May 2022) - Huang, Jiahui; Zhang, Dan; Chen, Yanhan; Yu, Chengfu; Zhen, Shuangju; Zhang, Wei
Highlights: Parental psychological control has been shown to be associated with adolescent NSSI. Psychological need satisfaction mediate the relationship between parental psychological control and adolescent NSSI. Sensation seeking moderate the association between unmet psychological needs and adolescent NSSI. Intervention programs aimed at reducing adolescent NSSI may benefit from this study. Abstract: Parental psychological control has been shown to be associated with adolescent non-suicidal self-injury (NSSI). However, little is known about the mediating and moderating mechanisms underlying this relationship. Self-determination theory and previous research provided the framework for our hypotheses about these processes. This study test the mediating effect of psychological need satisfaction between parental psychological control and adolescent NSSI, and whether this mediating effect was moderated by sensation seeking. A sample of 1006 adolescents ( Mage = 13.16 years; SD = 0.67 years) anonymously completed questionnaires assessing the study variables. The results of structural equation modeling showed that as expected, the positive association between parental psychological control and adolescent NSSI was mediated by low satisfaction of the psychological needs. Also as expected, this indirect link was stronger among adolescents high in sensation seeking. The results are consistent with the self-determination theory's assumption that psychological need satisfaction as a potential mechanism linking parental psychological control to adolescent NSSI, and high sensation seeking as an important risk factor that amplifies this indirect effect. Intervention programs aimed at reducing adolescent NSSI may benefit from this study, such as Dialectical Behavior Therapy.